The Influence Of Posyandu Cadre Roles, Nutrition Education By Puskesmas Officers, And Mother's Compliance In Providing Complementary Feeding On The Incidence Of Toddler Stunting: Survey In The Cisaga Puskesmas Area, Ciamis Regency - Nurfitriani, Astrid; Kosasih; Rahmiyati, Ayu Laili (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aimed to analyze the influence of Posyandu cadres’ roles, nutrition education by health center officers, and maternal compliance in complementary feeding on stunting among toddlers. A quantitative descriptive-verificative method was applied to 95 respondents selected using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression. Results showed all variables simultaneously had a significant effect on stunting (Sig.<0.05; R²=0.840). Partially, cadre roles and maternal compliance had positive significant effects, while nutrition education showed a negative but significant effect. Collaboration among cadres, health workers, and families is essential for effective stunting prevention.